Comparison of RAPD, ISSR and SSR markers in assessing genetic diversity among rye*(Secale cereale L.) inbred lines - Myśków , Beata; Milczarski, Paweł; Masojc, Piotr (Plant Breeding and Seed Science, 2010)
Forty eight inbred lines of winter rye, of various origin and pedigree, were analysed using 19 RAPD (random amplified polymorphic DNA) primers, 8 ISSR (inter-simple sequence repeats) primers and 13 SSR (simple sequence repeats) primer pairs. On the basis of particular marker types, there were created three separate dendrograms and one combined similarity tree, prepared on account of the whole data. Correlation coefficients for individual technique based on genetic similarity matrices were not significant. By comparing the GS data obtained on the basis of singular methods with collective matrix, it was observed that the highest correlation rate was for ISSR method (r=0.68). The utility of each marker technique was compared by using marker index MI. Diversity detecting index (DDI) was suggested in the paper, which may prove helpful in planning and comparing researches on phenetic relationships...